Involvement of role of HMGB1-NLRP3 pathway in systemic disorders - Yang, Lei; Li, Xue; Zhu, Xiaoming; Ge, Futao; Wang, Yuantao (Frontiers in Cell and Developmental Biology, 2025)
High mobility group box-1 (HMGB1) is a protein released from stressed or damaged cells that triggers immune activation and chronic inflammation. The NOD-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) is a central component of the inflammasome, which activates caspase-1 and releases pro-inflammatory cytokines, including IL-1β and IL-18. The HMGB1/NLRP3 axis plays a critical role in regulating inflammation and immune responses, driving systemic inflammation and disease progression. Targeting this pathway offers promising therapeutic strategies for conditions such as autoimmune disorders, trauma, and chronic inflammatory diseases. In particular, inhibiting HMGB1 or NLRP3 can mitigate the exaggerated inflammatory response, reduce tissue damage, and slow disease progression. This review explores the bidirectional interactions between HMGB1 and NLRP3 and discusses current and emerging therapeutic approaches targeting this axis to modulate inflammation and improve clinical outcomes.